Analiza vpliva orientacije ojačitvenih vlaken na natezne lastnosti večplastnih polimernih kompozitov - Lavrič, Aleš (Kovine zlitine tehnologije, 1998)
Multi-ply polyester composites manufactured "manually" have taken an important position in engineering applications. A significant feature of these composites is that their mechanical properties can be changed locally, by way of their fiber volume fraction, ply number and ply arrangement. Optimum mechanical properties of a structural element or a structure can be achieved in this way. The paper presents the analysis of the influence of the mentioned parameters upon tensile properties of composite material. Guidelines will be given, by means of which an engineer can easily prescribe the lamination model with regard to local stress or strain condition, determined with the method limit or boundary elements.
Keywords: kompoziti; poliester; steklena vlakna; trdnost